Consumer acculturation and reacculturation experience: Taiwanese returnees' negotiation of roles and identity through dress - Zarubin, Tracy, author; Yan, Ruoh-Nan, advisor; Ogle, Jennifer, committee member; Kwiatkowski, Lynn, committee member (Colorado State University. Libraries, 2015)
The purpose of this interpretive study is to qualitatively analyze the process of consumer acculturation and reacculturation through consumption practices related to dress by which Chinese women from Taiwan negotiated their roles and identity in their home culture (Taiwan), host culture (United States) and upon returning to their home culture (Taiwan). This study focuses on these womens' experiences as they moved across cultures, specifically looking at their perception of home and host culture, dress strategies, cultural value orientation, and how these influenced their consumer acculturation and reacculturating outcomes. Based on the findings of this study, a consumer acculturation model for returnees has been developed. This model reflects these womens' experiences as they transitioned across two different cultures, highlighting factors that contributed to the outcomes of assimilation, maintenance and resistance. This study found that the reacculturation process was a much harder transition than acculturating to a host culture because participants were undergoing a major role transition from student to working professional and they had no expectations of what this life would be like, making it difficult to adjust. Also, segregation was altogether not an outcome. This research provides new insights into the complex and dynamic process of consumer acculturation and reacculturation of women as they transition from home to host and back to home culture.
Keywords: consumer acculturation; consumption practices; cultural value orientation; reacculturation; role identity; Taiwanese women